Enabling Green and Blue Infrastructure to Improve Contributions to Human Well-Being and Equity in Urban Systems. (26th June 2019) - Andersson, Erik; Langemeyer, Johannes; Borgström, Sara; McPhearson, Timon; Haase, Dagmar; Kronenberg, Jakub; Barton, David N; Davis, McKenna; Naumann, Sandra; Röschel, Lina; Baró, Francesc
Abstract: The circumstances under which different ecosystem service benefits can be realized differ. The benefits tend to be coproduced and to be enabled by multiple interacting social, ecological, and technological factors, which is particularly evident in cities. As many cities are undergoing rapid change, these factors need to be better understood and accounted for, especially for those most in need of benefits. We propose a framework of three systemic filters that affect the flow of ecosystem service benefits: the interactions among green, blue, and built infrastructures; the regulatory power and governance of institutions; and people's individual and shared perceptions and values. We argue that more fully connecting green and blue infrastructure to its urban systems context and highlighting dynamic interactions among the three filters are key to understanding how and why ecosystem services have variable distribution, continuing inequities in who benefits, and the long-term resilience of the flows of benefits.